An Innovative Odd-Power Divider by means of a Triple FinLine Waveguide to Microstrip Transition - S. Fantauzzi; L. Valletti; D. Passi; F. Di Paolo (Advanced Electromagnetics, 2022)
This paper outlines a novel approach to design a waveguide to microstrip Finline transition, that allows a division by three of the RF power traveling inside a rectangular waveguide. The possibility of obtaining and odd power division of microwave and millimeter wave signals with such Finline transition is completely unexplored yet harbinger of great opportunities. Starting from a 3D CAD model of the structure and continuing with Electromagnetic simulations, the obtained results completely describe a transition able to achieve an almost perfect power splitting by three. Multyphisics simulations, show an intrinsic resistance to vibrations of such transition, allowing it to be installed on aircraft or satellites modules. Thanks to this achievement a total new kind of power devices will come next, exploiting this odd power division in fact, it will be possible to realize different types of microwave amplifiers, increasing the efficiency and decreasing the occupied size. At the Author’s best knowledge it is the first time a divider by three Finline transition is reported in literature.